GENDER AND POLITENESS VARIATION IN LANGUAGE FOR WOMEN AND MAN - Yuni Lutfiah; Kholijah, Annisa Nur; Nurresta, Pratiwi; Rofiqi, Fauzan; Nargis, Nargis (VARIABLE RESEARCH JOURNAL, 2025)
Language reflects societal and cultural norms, including how politeness and gender variations are expressed. Women often use formal and polite language, highlighting empathy and gentleness, while men tend to prefer direct and informal expressions, emphasizing assertiveness. This pattern is influenced by social norms and can be observed in various languages, such as Japanese and Indonesian. In Japanese, gender differences are evident in grammar and vocabulary. Meanwhile, although Indonesian lacks grammatical gender distinctions, women frequently use polite expressions like "sorry," "please," and "thank you" more than men. Politeness in language is closely tied to societal hierarchies and traditional gender roles, shaping daily communication. These linguistic differences reinforce cultural expectations and social structures, highlighting the role of language in reflecting and perpetuating gender norms. Understanding this dynamic provides valuable insights into how language and culture interact to shape human interaction.